Impact of Entrepreneurship on Unemployment and Poverty Reduction: The Case of Bukavu in DR Congo - Karhamikire, Paul Kadundu; Ngangura, Christian Mwemezi; Nankafu, Nicole-Adams (International Journal of Economics and Financial Issues, 2024)
The Democratic Republic of the Congo (DRC) grapples with severe poverty and unemployment issues, necessitating a focus on factors that can alleviate both challenges. This study specifically examines the impact of entrepreneurship on poverty reduction and unemployment in Bukavu. Through a comprehensive literature review and data analysis using a linear regression on cross-sectional data, the research reveals a trend with individuals transition from employment to entrepreneurship, particularly after completing studies, leading to a decline in the unemployment rate since 2015. Entrepreneurs also exhibit lower poverty indicators compared to non-entrepreneurs. The study recommends implementing measures, such as tax relief and entrepreneurial education, to encourage entrepreneurship, thereby creating employment opportunities and addressing poverty and unemployment in Bukavu.